Literatur Review: Faktor Resiko Sindrom Ovarium Polikistik pada Remaja: Literature Review: Risk Factors for Polycystic Ovary Syndrome in Adolescents - Wilda Qotrunnada Salsabila; Kartika Adyani; Friska Realita (LPPM STIKES Guna Bangsa Yogyakarta, 2024)
Polycystic ovary syndrome (PCOS) is a complex metabolic, reproductive, and psychological disorder that impacts women throughout their lives. PCOS is a hormonal imbalance disorder that occurs in women of childbearing age. This can cause symptoms such as irregular menstruation, amenorrhea (absence of menstruation), anovulation (absence of ovulation), hirsutism, acne, and obesity. PCOS also causes metabolic disorders in the body. The exact cause of PCOS is not known but in general it can be caused by genetic and environmental factors. Many studies have proven the factors that influence PCOS. Therefore, to conclude the results of this research, a literature review was carried out. The literature was searched for scientific articles with the keywords